Technical efficiency of garlic production under rain fed agriculture in Northwest Ethiopia: Stochastic frontier approach - Fasika Chekol; Kindie Abetie; Teshome Sirany (Cogent Economics & Finance, 2023)
The article focuses on evaluating the technical efficiency of garlic production in northwest Ethiopia. The average yield in the region was lower than its potential, indicating a need to improve farming practices. Data were collected from 359 garlic producers using random sampling. The Cobb-Douglas stochastic frontier production function was used to estimate technical efficiency, which was found to be 73%. This means that about 27% of potential garlic output was lost due to inefficiency. Factors such as land size, seed, fertilizer, insecticide, and oxen days were found to have a positive and significant impact on garlic production. On the other hand, factors like age, extension contact, distance, renting land, garlic disease shock, access to finance, and access to information were linked to technical inefficiency. The study suggests that investing in high-quality seeds, improved farming inputs, and access to information can enhance garlic output by leveraging its high efficiency level.
Keywords: 330; Cobb-Douglas; garlic; productivity; technical efficiency